Expanding the reach of probiotics through social enterprises - Reid, Gregor (2018)
The rapid rise in microbiome and probiotic science has led to estimates of product creation and sales exceeding $50 billion within five years. However, many people do not have access to affordable products, and regulatory agencies have stifled progress. The objective of a discussion group at the 2017 meeting of the International Scientific Association for Probiotics and Prebiotics was to identify mechanisms to confer the benefits of probiotics to a largerportion of the world?s population. Three initiatives, built around fermented food, were discussed with different methods of targeting populations that face enormous challenges of malnutrition, infectious disease, poverty and violent conflict. As new candidate probiotic strains emerge, and the market diversifies towards more personalised interventions, manufacturing processes will need to evolve. Information dissemination through scientific channels and social media is projected to provide consumers and healthcare providers with rapid access to clinical results, and to identify the nearest location of sites making new and affordable probiotic food and supplements. This rapid translation of science to individual well-being will not only expand the beneficiaries of probiotics, but also fuel new social enterprises and economic business models.